The effect of whey protein concentrates and hydrocolloids on the texture and colour characteristics of chicken sausages - Andres, Silvina Cecilia (2006)
The effects of fat reduction by increasing water content and the addition of whey protein and hydrocolloids on the instrumental texture profile, microstructure and water holding capacity of low‐fat chicken sausages were analysed. Low‐fat sausages were prepared with fresh breast chicken meat; in all formulations, a 3:7 ratio guar/xanthan gum was used. A factorial design with three levels of added fat (0%, 1.98% and 4.96%), two levels of whey protein concentrate (0.64% and 1.94%), and two levels of the hydrocolloids (0.13% and 0.32%) was applied. Samples were heat‐processed (73 °C final internal temperature) and, after cooling, chemical composition of the sausages was determined and scanning electron microscopic images were obtained. Colour was measured with a tristimulus reflectance colorimeter. Texture profile analysis of sausages was performed and the results were related to sample formulations. Extra‐lean products with a fat content lower than 0.5g/100g product showed very good quality attributes determined by a sensory panel.